Analisis Faktor-Faktor Yang Mempengaruhi Minat Menabung di Bank Syariah Kecamatan Perbaungan - Qorry Prananda Aulia; Ahmad Perdana Indra (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to analyze the influence of financial literacy, trust, location, income, and public views related to profit sharing in saving at Islamic banks. This type of research is qualitative and quantitative. Sampling techniques are simple random sampling and questionnaires. The results showed that financial literacy and location did not affect the interest in saving at Sharia Banks in the people of Perbaungan District. Trust, income and perception of profit sharing have a positive and significant effect on the interest in saving at Sharia Banks in the people of Perbaungan District. The need to expand the arrangement of data on Islamic banks such as sharia principles and products/goods in Islamic banks, so that interest in saving at Islamic banks will increase.